2015
DOI: 10.3748/wjg.v21.i37.10654
|View full text |Cite
|
Sign up to set email alerts
|

Histological healing after infliximab induction therapy in children with ulcerative colitis

Abstract: IFX has a positive histological effect in more than one-third of UC patients. IFX reduces intestinal inflammation and improves clinical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Data about the HR when using IFX are not so promising. D'haens et al [12] found that architectural alteration persisted in all adult UC patients reaching endoscopic remission under IFX, while significantly better results were obtained in pediatric UC patients [13]. Finally, we found that adult UC patients in deep remission under treatment with IFX failed to have a significant correlation with HR [6].…”
Section: Discussionsupporting
confidence: 51%
“…Data about the HR when using IFX are not so promising. D'haens et al [12] found that architectural alteration persisted in all adult UC patients reaching endoscopic remission under IFX, while significantly better results were obtained in pediatric UC patients [13]. Finally, we found that adult UC patients in deep remission under treatment with IFX failed to have a significant correlation with HR [6].…”
Section: Discussionsupporting
confidence: 51%
“…However, in our opinion, these elevated inflammatory markers in patients with quiescent IBD probably reflect ongoing IBD activity in the majority of patients. Indeed, many studies have shown that children and adults with IBD in clinical remission have ongoing inflammation on endoscopy [ 39 , 23 , 8 , 14 , 41 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, >30 histological scores have been developed, although their adoption in clinical practice remains modest 11 12. Similarly, different definitions and criteria of HR have been proposed, ranging from ‘elimination of mucosal ulceration/erosion’ to ‘complete histological normalisation’ 1 3 13–18. Almost all investigators now agree that the absence of neutrophilic infiltration (‘neutrophil-free’ mucosa) is the key to a HR definition due to its association with favourable clinical outcomes 2 4 5 19–22.…”
Section: Introductionmentioning
confidence: 99%